Identification and characterization of Clostridium botulinum strains associated with an infant botulism case in China. (February 2019) - Xin, Wenwen; Huang, Yong; Ji, Bin; Li, Ping; Wu, Ye; Liu, Jing; Wang, Xiaohong; Yang, Hao; Kang, Lin; Gao, Shan; An, Xiaoping; Xu, Xuefang; et al.
Abstract: Infant botulism was rarely reported in China. The second reported event of the disease including three cases occurred in 2015. In the present study, one (the third case) of the three cases was identified and investigated to trace the sources of transmission. Samples from feces and foodstuffs were used to isolate Clostridium botulinum strains. Each isolate was obtained from the baby's feces and opened powdered infant rice cereal, respectively. In this case, the C. botulinum strains were identified and characterized by combined mouse bioassay, Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and high-throughput sequencing including single nucleotide polymorphisms (SNP). Results showed that the disease was caused by a type B strain of C. botulinum . Strains associated with this case as well as isolates from stored and historical samples were phylogenetically analyzed and compared. C. botulinum type B isolates from the infant feces and from an opened container of infant rice cereal were indistinguishable, suggesting that opened container of infant rice cereal is likely to be the source of transmission of spores to the infant. It is not clear that how the opened container was contaminated and the child was exposed since environmental testing was not performed. This study provides detailed information about usage of the three methods and references for dealing with other associated cases. Highlights: An Infant Botulism Case was investigated. The disease was caused by a type B strain of C. botulinum. Mouse lethality assay, MALDI-TOF MS and high-throughput sequencing were used. The opened container of rice cereal is likely to be the source for transmission.